Стилист: [роман] / Александра Маринина - Маринина Александра Борисовна (Русский бестселлер, 2002)
Экземпляры: ф.14 (2003) / Инвентарный номер: 45792 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: М 26 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44